Public diplomacy of Japan in Central Asia: the examples of Uzbekistan and Kazakhstan (International relations and international law Journal, 2020)
This study focuses on the role of public diplomacy in shaping and implementing Japan’s foreign policy in Central Asia. Based on elements of cultural empathy, Japan creates an attractive image in Central Asia through the active use of public diplomacy resources and official development assistance. The central issue is that Japan uses public diplomacy in Central Asia more actively than is officially indicated.The dynamics of the development of foreign policy relations between Japan and Central Asia (CA) is examined by analyzing the examples of Kazakhstan and Uzbekistan, focusing on common areas of cooperation and manifestations of public diplomacy in the two countries. Qualitative research methods are used in work, including analysis of the content of documents and interviews. Both in the documents and responses in the interviews, in line with a constructivist approach to international relations, evidence was sought on how Japan identifies and promotes itself with the CA region and the countries concerned, and on the use of public diplomacy as a social power tool respectively.It was concluded that Japan has several areas of interest in Uzbekistan and Kazakhstan, including cooperation in the fields of education, economic development in the region, political reforms, and energy resources. Following Japan’s new initiative in 2015, the countries of Central Asia and Japan have established diplomatic ties and partnerships that continue to grow. Even though the analyzed documents seem to show that Japan’s interest in CA is low, the existence of implemented projects proves the opposite.